Обґрунтування необхідності оптимізації формування амортизаційної політики підприємств - Трачова, Дар'я Миколаївна; Трачева, Дарья Николаевна; Trachova, Daria (Вид-во Мелітопольська типографія «Люкс», 2017)
UK: У статті проведено аналіз формування амортизаційної політики України та її компонентів. Вивчено світовий досвід формування амортизаційної політики підприємств. Обґрунтовано необхідність оптимізації амортизаційної політки підприємств шляхом співставлення розміру амортизаційного фонду і інвестицій на модернізацію виробничих потужностей підприємства. Визначено подальший напрямок трансформації амортизаційної політики підприємства. EN: A comprehensive analysis of the formation amortization`s policy of Ukraine and its components. Determined that the depreciation policy of domestic enterprises formed nominally used primarily straight-line depreciation`s method. Proved that government regulation depreciation policy has a lot of contradictions Analyzed the share of depreciation in the company`s cost structure. Determined this figure hardly varies by year and approximately 7.5% of the total cost. At the same time analyzed the sources of investment companies of Zaporozhye region. Determined that the farms covered by depreciation of about 7.8% for capital investments. It is proved that at the time for the best agricultural enterprises step of forming the objective depreciation policy of revaluation of fixed assets.
Justification of the necessity optimization formation depreciation policy enterprises
Keywords: амортизаційна політика; бухгалтерський облік; інноваційний розвиток; облікова політика підприємства; економічна ефективність; depreciation; depreciation policy; financial and credit levers of enterprise development; state regulation; renewal of fixed capital; accounting